Integrasi Materi Fikih Jual Beli dalam Pembelajaran Fikih untuk Membentuk Kesadaran Ekonomi Siswa Madrasah Aliyah - M. Ikhsan Nur Effendi (Jurnal Manajemen dan Pendidikan Agama Islam, 2023)
Understanding the fiqh of buying and selling plays an important role in shaping the character of madrasah students who are honest, fair, and responsible in their daily economic activities. This article aims to examine the urgency of understanding the fiqh of buying and selling for madrasah students and its impact on their economic behavior. The study was conducted in one of the madrasah aliyah with a qualitative approach through observation, interviews, and documentation. The results show that understanding the fiqh of buying and selling can increase students' awareness of the importance of honesty and justice in economic transactions. However, challenges still exist in the process of internalizing fiqh values consistently in real life. Therefore, the role of teachers and contextual learning approaches are very important to strengthen the understanding and practice of fiqh of buying and selling among madrasah students.